Diskursus Perceraian Orang Tua dalam Novel Anak Indonesia dan Implikasinya terhadap Kompetensi Sosial Emosional Anak - Laila, Wahda Rahma; Ambarwati, Ari (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Parental divorce is a social phenomenon that greatly affects children’s development, particularly in their social and emotional aspects. This study aims to describe the representation of children’s experiences in coping with parental divorce in Indonesian children’s and young adult literature, as well as its implications for social-emotional competence. The research employed a qualitative method with a content analysis approach on three Indonesian literary works with divorce as the main theme: Seruni by Almas Sufeeya, Another Sorry by Fahrul Khakim, and the picture book Bagai Bumi Berhenti Berputar (As If the Earth Stopped Turning) by Clara Ng. The data, in the form of textual excerpts, were analyzed using Miles and Huberman’s model. The findings indicate that parental divorce is represented as having an impact on children’s interpersonal difficulties, emotional regulation, sense of loss, grief, and inner conflict. Seruni highlights emotional struggles and impulsive decisions; Another Sorry portrays sibling dynamics; while Bagai Bumi Berhenti Berputar presents a nurturing approach that supports children’s emotional stability. Positive representations reveal that parental support can reduce the negative effects of divorce. The analysis also shows alignment with the five dimensions of CASEL’s social-emotional competencies: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. Thus, children’s literature serves as both a reflective and educational medium to foster emotional development in children experiencing parental divorce.